Transdifferentiation of Human Hair Follicle Mesenchymal Stem Cells into Red Blood Cells by OCT4 - Zhijing Liu; Shi-Jiang Lu; Yan Lu; Xiaohua Tan; Xiaowei Zhang; Minlan Yang; Fuming Zhang; Yulin Li; Chengshi Quan (Hindawi Limited, 2015)
Shortage of red blood cells (RBCs, erythrocytes) can have potentially life-threatening consequences for rare or unusual blood type patients with massive blood loss resulting from various conditions. Erythrocytes have been derived from human pluripotent stem cells (PSCs), but the risk of potential tumorigenicity cannot be ignored, and a majority of these cells produced from PSCs express embryonic ε- and fetal γ-globins with little or no adult β-globin and remain nucleated. Here we report a method to generate erythrocytes from human hair follicle mesenchymal stem cells (hHFMSCs) by enforcing OCT4 gene expression and cytokine stimulation. Cells generated from hHFMSCs expressed mainly the adult β-globin chain with minimum level of the fetal γ-globin chain. Furthermore, these cells also underwent multiple maturation events and formed enucleated erythrocytes with a biconcave disc shape. Gene expression analyses showed that OCT4 regulated the expression of genes associated with both pluripotency and erythroid development during hHFMSC transdifferentiation toward erythroid cells. These findings show that mature erythrocytes can be generated from adult somatic cells, which may serve as an alternative source of RBCs for potential autologous transfusion.